Design and implementation of a wireless software-defined radio testbed radio testbed (2013)
Software-defi ned radio (SDR) provides a convenient framework for the design and implementation of a communication system, by separating the signal processing algorithms from the communication hardware. This separation allows researchers to design testbed systems to validate the gains in performance reported by the theory. Designing and implementing a testbed is a time consuming and challenging process. This work presents the design and implementation of a fl exible testbed system, including the solution to some synchronization problems. We also present a distributed software architecture that defi nes the control fl ow, the subsystem decomposition, and the mapping to hardware of the testbed. A running example of the testbed for a binary phase-shift keying (BPSK) system is developed to illustrate the results attained by the proposed testbed in terms of the performance comparison between the testbed measurements, and the theoretical and simulated ones with a loss of 2 dB.